In Vivo Histologically Equivalent Evaluation of Gastric Mucosal Topologic Morphology in Dogs By using Confocal Endomicroscopy. (5th March 2014) - Sharman, M.J.; Bacci, B.; Whittem, T.; Mansfield, C.S.
<x xml:space="preserve">Abstract</x> Background Confocal endomicroscopy (CEM) is an endoscopic technology permitting in vivo cellular and subcellular imaging. CEM aids real‐time clinical assessment and diagnosis of various gastrointestinal diseases in people. CEM allows in vivo characterization of small intestinal mucosal morphology in dogs. Objective To determine the feasibility of CEM to evaluate gastric mucosal morphology in dogs and to characterize the appearance in healthy dogs. Animals Fourteen clinically healthy research colony dogs. Methods Experimental study. Under general anesthesia, dogs underwent standard endoscopic evaluation and CEM of the gastric mucosa. In the initial 6 dogs, fluorescent contrast was provided with the fluorophore acriflavine (0.05% solution), applied topically. Subsequently, 8 dogs were assessed using a combination of fluorescein (10% solution, 15 mg/kg IV), followed by acriflavine administered topically. For each fluorophore, a minimum of 5 sites were assessed. Results Confocal endomicroscopy provided high quality in vivo histologically equivalent images of the gastric mucosa, but reduced flexibility of the endoscope tip limited imaging of the cranial stomach in some dogs. Intravenous administration of fluorescein allowed assessment of cellular cytoplasmic and microvasculature features. Topical application of acriflavine preferentially stained cellular nucleic acids, allowing additional evaluation of nuclear morphology. Identification of Helicobacter‐like organisms was possible in 13 dogs. Conclusion and Clinical Importance Confocal endomicroscopy provides in vivo images allowing assessment of gastric mucosal morphology during endoscopy, potentially permitting real‐time diagnosis of gastrointestinal disease.